2017
DOI: 10.3389/feart.2017.00067
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy Balance Closure and Turbulent Flux Parameterization on a Mid-Latitude Mountain Glacier, Purcell Mountains, Canada

Abstract: In the majority of glacier surface energy balance studies, parameterization rather than direct measurement is used to estimate one or more of the individual heat fluxes, with others, such as the rain and ground heat fluxes, often deemed negligible. Turbulent fluxes of sensible and latent heat are commonly parameterized using the bulk aerodynamic technique. This method was developed for horizontal, uniform surfaces rather than sloped, inhomogeneous glacier terrain, and significant uncertainty remains regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(117 citation statements)
references
References 57 publications
(91 reference statements)
9
107
1
Order By: Relevance
“…Without an adequate model for u * , the use of the stability corrections for Q H will likely fail. Similar findings derived from a different glacier in this region (Fitzpatrick et al, 2017) suggest the transferability of this finding to other mountain glaciers subject to similar climate.…”
Section: Discussionsupporting
confidence: 85%
“…Without an adequate model for u * , the use of the stability corrections for Q H will likely fail. Similar findings derived from a different glacier in this region (Fitzpatrick et al, 2017) suggest the transferability of this finding to other mountain glaciers subject to similar climate.…”
Section: Discussionsupporting
confidence: 85%
“…Steep winter SWE gradients characterized both glaciers throughout the study period (115-440 mm 100 m −1 ). Such gradients are comparable to previous results for glaciers in the region (Pelto et al, 2013;McGrath et al, 2015), but exceed reported orographic precipitation gradients in other mountainous regions by a factor of 2-3 (e.g., Anderson et al, 2014;Grünewald and Lehning, 2011). These steep gradients are likely the result of physical processes beyond just orographic precipitation, including storm systems that deliver snow at upper elevations and rain at lower elevations (common at both Wolverine and Gulkana) and mid-winter ablation at lower elevations (at Wolverine).…”
Section: Elevationsupporting
confidence: 82%
“…Estimates of end-of-season snow density introduce a possible bias, but given the regional consistency of late summer snow density and the overall lack of a density-altitude gradient in spring, using a single snow density is a robust method for converting snow depth to water equivalence (Fausto et al, 2018;McGrath et al, 2018). We observed greater variability in B s relative to B w , highlighting the need for models of glacier mass balance that can be able to reliably reproduce widely varying rates of mass change corresponding to the multitude of energy fluxes that influence alpine glaciers (Fitzpatrick et al, 2017).…”
Section: Mass Change Between Measurementsmentioning
confidence: 89%